Practical Application of The Teachings of Apostle Paul Regarding The Divine Calling to Serve, as Outlined in 1 Timothy 4:1-8 on The Christian Teachers Within The Jabodetabek Area - Gurning, Lasmauli; Wahyuni, Sri; M.Iskandar, Srini; Uriptiningsih, Ana Lestari (Green Publisher Indonesia, 2023)
Calling to Serve is the duty of a servant of God, including Christian teachers. The form of the task and call is to serve the preaching of the Word regardless of the conditions, admonish and advise, also provide sound teaching. At the research locus, researchers found that Christian teachers who had implemented the call to serve in their learning activities were teachers who were civil servants or certified, while teachers who taught general subjects had not implemented the call to serve. At the research locus, the researchers also found that there were teachers whose educational qualifications were not linear, teachers in the field of biology studies became teachers of Christian Religious Education because they were Christians. It was also found that teachers were impatient with students and even lacked self-control. In addition, there are some teachers who are not called to serve as teachers, because their parents or siblings have become teachers. In the end, they also become teachers. Some teachers have different backgrounds. Based on these findings, the researcher considers it necessary to research the call to ministry because as Christian teachers the call to serve based on 2 Timothy 4:1-8 is very important.